ВИДАВНИЧА ПОЛІТИКА ЖУРНАЛУ «ТЕХНІЧНА ЕЛЕКТРОДИНАМІКА» – ДОТРИМАННЯ ПРИНЦИПІВ АКАДЕМІЧНОЇ ДОБРОЧЕСНОСТІ - Городжа, Л.В. (Інститут електродинаміки НАН України, Київ, 2021)
The main principles of the publishing policy of the journal "Technical Electrodynamics" are considered, namely the observance of the principles of academic integrity. The concept of academic integrity, types of its violation - plagiarism, self-plagiarism, falsification, fabrication are explained. There are some legal documents developed in Ukraine on this issue, which must be followed by every scientist and scientific publications. References 10